2017
DOI: 10.1002/iub.1678
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of syndecan 2 in epithelial and mesenchymal cancer progression

Abstract: Syndecan 2 (SDC2) belongs to a four-member family of evolutionary conserved small type I transmembrane proteoglycans consisting of a protein core to which glycosaminoglycan chains are covalently attached. SDC2 is a cell surface heparan sulfate proteoglycan, which is increasingly drawing attention for its distinct characteristics and its participation in numerous cell functions, including those related to carcinogenesis. Increasing evidence suggests that the role of SDC2 in cancer pathogenesis is dependent on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 91 publications
2
52
0
Order By: Relevance
“…Syndecan-2 protein, encoded by the SDC2 gene, is a type I transmembrane proteoglycan. The role of SDC2 depends on the type of tumor: it acts as an oncogene and contributes to disease progression in colon cancer, breast cancer and melanoma, while it serves as a metastasis suppressor in Lewis lung carcinoma [39][40][41]. Moreover, SDC2 has been found to be positively associated with the differentiation level and prognosis of neuroendocrine tumors, which is consistent with our ndings [42].…”
Section: Disscussionsupporting
confidence: 89%
“…Syndecan-2 protein, encoded by the SDC2 gene, is a type I transmembrane proteoglycan. The role of SDC2 depends on the type of tumor: it acts as an oncogene and contributes to disease progression in colon cancer, breast cancer and melanoma, while it serves as a metastasis suppressor in Lewis lung carcinoma [39][40][41]. Moreover, SDC2 has been found to be positively associated with the differentiation level and prognosis of neuroendocrine tumors, which is consistent with our ndings [42].…”
Section: Disscussionsupporting
confidence: 89%
“…HSPGs have also been shown to influence cancer exosome shedding and uptake, thereby modulating cell-to-cell communication between cancer and healthy fibroblasts, immune cells, and endothelial cells (150, 151). HSPGs can also influence actin cytoskeleton remodeling and cancer cell motility (95). The HSPG, SDC2 binds Ezrin, a cytoskeletal protein (152) and serves as adapter molecules for IGF1 mediated activation of ERK (95).…”
Section: Resultsmentioning
confidence: 99%
“…HSPGs can also influence actin cytoskeleton remodeling and cancer cell motility (95). The HSPG, SDC2 binds Ezrin, a cytoskeletal protein (152) and serves as adapter molecules for IGF1 mediated activation of ERK (95). Additionally, HSPGs are implicated in lipoprotein uptake and cellular stress signaling (153, 154).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that syndecan 2 is a conduit point for signals originating in extracellular matrix capable, through exquisitely regulated downstream mechanisms, to regulate cancer cell functions. Studies on syndecan 2 pinpoint this proteoglycan as a potential target for cancer treatment .
…”
mentioning
confidence: 99%